Analysis of the Needs for Using Digital Comics with Local Wisdom to Increase ReadingLiteracyin ElementarySchoolStudents - Wulandari, Dwi; Rejekiningsih, Triana; Santosa, Eka Budhi (Universitas Sebelas Maret, 2023)
Reading literacy is the capacity to comprehend and make use of the written forms of communication required by society. Despite the fact that reading literacy is crucial, many individuals still disregard it and should begin in elementary school. The purpose of this study was to learn more about how local wisdom-based digital comics are used as a teaching tool for elementary school students, as well as about the challenges they face in developing their reading literacy and the learning media formulations that need to be developed. The findings of the observations were compiled into a tool for determining primary school pupils' requirements, which was then descriptively and qualitatively examined. When doing qualitative research utilizing the descriptive technique, teachers and students are observed and their data is thoroughly examined. Based on the findings of this study, it can be said that learning materials regarding digital comics that are grounded in local knowledge are crucial for fostering students' interest in reading.